2015
DOI: 10.1158/2159-8290.cd-15-0013
|View full text |Cite
|
Sign up to set email alerts
|

Sweets for a Bitter End: Lung Cancer Cell–Surface Protein Glycosylation Mediates Metastatic Colonization

Abstract: Summary Glycosylation is one of the most predominant forms of cell surface protein modifications and yet its de-regulation in cancer and contribution to tumor microenvironment interactions remains poorly understood. In this issue of Cancer Discovery, Reticker-Flynn and Bhatia characterize an enzymatic switch in lung cancer cells that triggers aberrant surface protein glycosylation patterns, adhesion to lectins on the surface of inflammatory cells, and subsequent metastatic colonization of the liver.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…30,31 Different levels of expression of glycans on the surface of cancer cells have caused differences in their metastasis. 32,33 Numerous studies on glycoproteins, especially α2, 6-linked Sias, have shown that the survival rate of cancer patients and their prognosis are closely related to this glycoprotein. 33 Therefore, with sufficient information about the properties of glycan epitopes, it can be used to target proteins and glycans.…”
Section: Discussionmentioning
confidence: 99%
“…30,31 Different levels of expression of glycans on the surface of cancer cells have caused differences in their metastasis. 32,33 Numerous studies on glycoproteins, especially α2, 6-linked Sias, have shown that the survival rate of cancer patients and their prognosis are closely related to this glycoprotein. 33 Therefore, with sufficient information about the properties of glycan epitopes, it can be used to target proteins and glycans.…”
Section: Discussionmentioning
confidence: 99%
“…Differential surface expression of glycans helps cancer cells in gaining invasive advantage. 42 , 43 Evidences suggest, increase in the endogenous levels of sialylated glycoproteins especially α 2,6-linked Sias, correlate with poor prognosis and survival rate of carcinoma patients. 44 , 45 This unique profile of glycan epitopes can thus be used as ideal candidates to be targeted by specific bait proteins, lectins.…”
Section: Discussionmentioning
confidence: 99%
“…Complex network of sugar residues (glycocalyx) comprises a major part of the ECM, mediating various social events like cellular adhesion, motility and signaling. 4 Although recent advancement of glycomics reportedly link aberrant glycosylation with cancer progression 4 , 5 , 6 , 7 , 8 , 9 albeit necessary insights emphasizing its importance in the perspective of progression of OC are still not available.…”
mentioning
confidence: 99%
“…The upregulation of sialic acid sugars attached to glycoproteins and glycolipids has become a hallmark of several tumor cell types [331]. As metastasis and invasion depend on extracellular matrix (ECM) molecules like ECM cytokines, growth factors, and cell surface proteins, their altered glycosylation has been shown to induce contact-dependent mechanisms that allow tumor cell extravasation [332]. Specifically, gliomas, which are challenging due to their invasiveness [333], bind hyaluronic acid-based ECM to interact with the lectican family chondroitin sulfate proteoglycans and CD44 [334,335] that are involved in tumor migration.…”
Section: Glycomics and Glycoproteomics In Cancer Studiesmentioning
confidence: 99%